DISEMINASI TEKNOLOGI BUDIDAYA UDANG VANAME SKALA RUMAH TANGGA BACKYARD SHRIMP FARMING (BSF) - Annisa Bias Cahyanurani; Nasuki Nasuki; Atika Marisa Halim; Lusiana BR. Ritonga; Asep Akmal Aonullah; Putri Nurhanida Rizky; Kartika Primasari (Universitas Mataram, 2023)
The vannamei shrimp farming business still has the opportunity to continue to develop given the public's high demand and high national shrimp production target that must be met. Vannamei shrimp is also a commodity that has high economic value. However, vannamei shrimp cultivation is known as cultivation which requires the cultivators to have large capital making it difficult for all groups to reach. The purpose of this community service activity is to provide information and insight to the public regarding shrimp farming with technology that can be applied on a small scale with relatively low capital and is expected to be accessible to all people who wish to cultivate vannamei shrimp using a household scale cultivation system (Backyard Shrimp Farming/BSF). This service activity is in the form of online dissemination using the zoom application and broadcast live via YouTube of the Politeknik Kelautan dan Perikanan Sidoarjo. The activity was carried out by delivering material by the speaker and followed by a discussion and question and answer between the participants and the speaker. At the end of the activity, participants were given a link to fill out an assessment questionnaire related to the dissemination activities carried out. Based on the results of the questionnaire, it can be concluded that the participants had a great interest in this household-scale vannamei shrimp farming opportunity and felt the benefits of this dissemination activity, and overall the dissemination had been carried out well in terms of clarity of material delivery, the interaction between participants and the speaker, the suitability of the material and the performance of the moderator/facilitator in presenting the event.